2019
DOI: 10.26444/aaem/102293
|View full text |Cite
|
Sign up to set email alerts
|

Human toxocariasis seroprevalence among patients with uveitis in Alborz Province, Iran

Abstract: Introduction and objective. Toxocariasis, predominantly caused by Toxocara canis, is a common zoonotic parasitosis worldwide. Toxocara infection is a cause of vision impairment and blindness. The presented study investigates the frequency of antibodies against Toxocara among uveitis patients and the epidemiological factors associated with disease. Materials and method. Fifty-four patients with uveitis and 59 healthy subjects were studied. Anti-Toxocara antibodies status was determined in all serum samples usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…Also, the country is a mountainous region with several mountain ranges, mostly located at the western and northern parts such as Zagros mountain ranges with colder winters and heavy snowfalls. The annual precipitation is 680 mm in the eastern part of the plain and more than 1700 mm in the western parts [18][19][20][21].…”
Section: Study Areamentioning
confidence: 99%
“…Also, the country is a mountainous region with several mountain ranges, mostly located at the western and northern parts such as Zagros mountain ranges with colder winters and heavy snowfalls. The annual precipitation is 680 mm in the eastern part of the plain and more than 1700 mm in the western parts [18][19][20][21].…”
Section: Study Areamentioning
confidence: 99%
“…Transmission to humans occurs by ingestion of embryonated Toxocara spp. eggs in the soil, water and vegetables, or through contaminated hands and fomites, and/or eating the meat of paratenic hosts containing encapsulated larvae [1][2][3][4][5]. Most infections do not have any clinical symptoms, athough Toxocara larvae are released within the different tissues and organs and may cause dangerous clinical syndromes, including weight loss, fever with a cough and shortness of breath, generalized lymphadenopathy and hepatomegaly [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study that confirms that OT can be observed in patients with uveitis in Mashhad, Iran. There have been few reports of OT from Iran ( 13 , 14 ). Most of the OT cases were reported from Caspian Sea coastal areas ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been few reports of OT from Iran ( 13 , 14 ). Most of the OT cases were reported from Caspian Sea coastal areas ( 14 ). In the present study, one of patients came from this area.…”
Section: Discussionmentioning
confidence: 99%